Influence of price, product quality, location and promotion on purchasing decisions of Cinta Air Hitam Langkat chips - Ilham Rahmat (Central Research Institute for Agriculture (CeRIA), 2023)
This study aims to analyze the effect of price, product quality, location and promotion on purchasing decisions. The research method used is a quantitative method. This study uses purposive sampling. The sample in this study amounted to 50 respondents. Data collection instrument using a questionnaire. The data analysis method used is multiple linear regression. All statements are valid, reliable and normal. The results show that the coefficient of determination (R Square) of the independent variable on the dependent variable is R2 = 0.821 or 82.1%. The independent variable can explain the dependent variable. From the research, it shows that price has a significant effect on the decision to buy Air Hitam Langkat love chips. This is proven by tcount being greater than ttable (2.523 > 2.014). And product quality has a significant effect on purchasing decisions of Air Hitam Langkat love chips. This is evidenced by tcount being greater than ttable (5.120 > 2.014). Meanwhile, location has no significant effect on the decision to buy Air Hitam Langkat love chips. This is evidenced by tcount which is smaller than ttable (-1.035 <2.014). And so does the promotion, which has no significant effect on the decision to buy Air Hitam Langkat love chips. This is evidenced by tcount which is smaller than ttable (0.389 <2.014). While the results of the simultaneous test of price, product quality, location and promotion variables have a significant effect of fcount 51.639 > ftable 2.58 on purchasing decisions. This shows that the better the price, product quality, location and promotion provided, the higher the purchasing decision of Cinta Air Hitam Langkat Chips.